2014
DOI: 10.5539/jfr.v3n6p124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermented Winery By-Product Supplemented Rations on the Temperament and Meat Quality of Angus-Hereford X Steers During Feeding in a British Columbia Feedlot

Abstract: Novel value-added beef products provide improved product differentiation within the beef marketplace. This study evaluated the impacts of supplementing feeds with fermented winery by-products (WB) to produce the novel beef product labeled by industry as "wine-finished beef". To evaluate the impact of this feed, a total of 69 Angus-Hereford X steers were placed in four pens (n=18,17,17,17), one replicate pen per treatment, and fed finishing rations containing equal amounts of either 6-7% WB or 6-7% water (Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
4
2
0
Order By: Relevance
“…The DGP supplementation did not significantly affect feed intake, life weight, carcass weight, and the carcass yield, presumably due to the absence of variations in the energy balance of diets. These results are in agreement with what has been previously reported by Moote et al (2014) who tested on steers a dietary supplementation with fermented winery by-product [21]; similar results were obtained also on lambs, although in this case authors highlighted an increase of bone weight after a dietary supplementation of 10% GP, a finding that was justified, at least in part, by the flavonoids ability to enhance osteoblasts differentiation and inhibit the osteoclasts function [22].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The DGP supplementation did not significantly affect feed intake, life weight, carcass weight, and the carcass yield, presumably due to the absence of variations in the energy balance of diets. These results are in agreement with what has been previously reported by Moote et al (2014) who tested on steers a dietary supplementation with fermented winery by-product [21]; similar results were obtained also on lambs, although in this case authors highlighted an increase of bone weight after a dietary supplementation of 10% GP, a finding that was justified, at least in part, by the flavonoids ability to enhance osteoblasts differentiation and inhibit the osteoclasts function [22].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, with regard to the chemical composition of meat samples, the dietary DGP supplementation did not induce significant variations, confirming the evidence previously reported in a similar study on steers, conducted by Moote et al (2014) [21].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In one study, Macias [79] reported an increase in carcass pH up to 45 min postmortem with the dietary inclusion of Ferulic acid from winery by-products in ruminant diets. Several studies have reported that carcass traits were not affected by dietary inclusion of citrus and winery by-products in ruminant diets, except for dressing percentage, which was reduced with the addition of these fruit by-products in ruminant diets [50,[80][81][82][83]. In another trial, Kafantaris [76] observed that an inclusion level of up to 100 g/kg DM of citrus and winery by-products in ruminant diets increased slaughter, warm, and cold carcass weights and longissimus muscle area.…”
Section: Effects On Growth Performance and Carcass Traitsmentioning
confidence: 99%
“…Grape meal products at inclusion levels between 5% and 20% have been shown to improve some aspects of ruminant production (Hadjipanayiotou and Locuca, 1976;Moate et al, 2014;Moote et al, 2014;Voicu et al, 2014;AWRI, 2016). Its feeding value has been found to be comparable to hay or straw (Winkler et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%